Participant‐Reported Benefits of Involvement in an Adaptive Sports Program: A Qualitative Study. Issue 5 (27th October 2017) - Lape, Emma C.; Katz, Jeffrey N.; Losina, Elena; Kerman, Hannah M.; Gedman, Marissa A.; Blauwet, Cheri A.
Abstract: Background: Although participation in adaptive sports offers numerous benefits for persons with disabilities, a substantial number of eligible persons do not take part. Previous studies have identified personal and environmental factors that promote or inhibit adaptive sports participation. However, these studies have considered a relatively narrow range of factors. Objective: To use qualitative research techniques to identify novel factors that influence participation in a community‐based adaptive sports program. Design: Qualitative focus group study. Setting: Community‐based adaptive sports programs affiliated with a rehabilitation hospital network. Participants: Participants were recruited from among 134 adults who registered for the sports program in 2013‐2014. Participants with mobility or sensory impairment, absence of cognitive impairment, and English proficiency were included. The 90 former participants with adequate contact information were contacted, and 17 participated in the focus groups. Methods: Two moderators led each of 3 audio‐recorded focus groups using a moderator's guide. We conducted a thematic analysis of transcript data to identify perceived benefits, barriers, and facilitators of participation. Results: Our analysis identified 5 themes: physical well‐being and health/safety; interpersonal and social relationships; intrapersonal and beliefs/attitudes; physical environment; and access. Participants experienced participation both as physically beneficial and as transformative in terms of how they view themselves. However, programs drew on limited personal resources and sometimes presented a perceived risk of injury. Finding information about and transportation to programs was a challenge. Participants formed an informal community that modeled what athletes with disabilities are capable of, helping to overcome initial doubts. Conclusions: To gain the benefits of participation, athletes overcame significant barriers, several of which may be modifiable, including transportation and difficult‐to‐find information about program offerings. The importance of community and raising awareness of athletes' own abilities suggests a key role for mentorship. Our study contributes to the understanding of experiential aspects that motivate participation in adaptive sports. Level of Evidence: IV